Exposure‐safety and exposure‐efficacy analyses for tisotumab vedotin for patients with locally advanced or metastatic solid tumors - Chaitali Passey; Jenna Voellinger; Leonid Gibiansky; Rudy Gunawan; Leonardo Nicacio; Ibrahima Soumaoro; William D. Hanley; Helen Winter; Manish Gupta (Wiley, 2023)
Abstract The antibody‐drug conjugate (ADC) tisotumab vedotin (TV) received accelerated approval from the US Food and Drug Administration for treatment of adults with recurrent or metastatic cervical cancer (r/mCC) with disease progression on or after chemotherapy. A population pharmacokinetic (PK) model, developed using dosing data from four clinical TV studies, was used to estimate individual exposure and explore safety and efficacy exposure‐response (ER) relationships. Because PK analysis showed no appreciable accumulation of TV and monomethyl auristatin E (MMAE) with repeated dosing, cycle 1 exposure metrics and predicted average concentrations from time zero until end of the cycle in which an event occurred (CavgLast) were used for ER analyses. The probability of achieving objective response increased significantly as the ADC cycle 1 maximum serum concentration (Cmax) increased. The probability of treatment‐related adverse events (AEs) leading to dose modification increased significantly as ADC cycle 1 area under the concentration‐time curve (AUC) increased. Number of grade 2+ ocular AEs increased significantly as ADC cycle 1 AUC, Cmax, and ADC CavgLast increased. MMAE cycle 1 AUC predicted risk of serious treatment‐related AEs. The relationship between ADC exposure and efficacy end points suggests ADC treatment was associated with clinically meaningful response across the observed exposures; greater exposure was associated with increased efficacy. The relationship between ADC and MMAE exposure and safety end points suggests increased exposure was associated with increased AE risk. These results align with clinical findings showing TV 2 mg/kg (≤200 mg for patients ≥100 kg) every 3 weeks is efficacious and tolerable for patients with r/mCC.